Optical Properties of Nested Pyramidal Nanoshells - Lin, Julia Y. (2010)
This paper describes the fabrication and characterization of nested Au pyramidal nanoshells. These particles exhibited two plasmon resonances at visible and near-infrared wavelengths that could be manipulated depending on the size of the gap between inner and outer pyramidal shells. We found that larger gaps (30 nm) exhibited much larger Raman scattering responses compared to smaller gaps (5 nm) in the nested pyramidal shells. The SERS-activity of these anisotropic particles can be optimized by adjusting the distances between the inner and outer Au shells.